2022
DOI: 10.3390/jpm12081227
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Selected miRNAs as Diagnostic, Predictive and Prognostic Markers in Non-Small-Cell Lung Cancer

Abstract: Lung cancer remains a leading cause of cancer-related deaths worldwide, overtaking colon, breast, and prostate cancer-related deaths. Due to the limited diagnostic possibilities, it is often diagnosed after it has reached an advanced stage. The delayed diagnosis significantly worsens the patient’s prognosis. In recent years, we have observed an increased interest in the use of microRNAs (miRNAs) as diagnostic, predictive, and prognostic markers in non-small-cell lung cancer (NSCLC). The abnormal expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Studies have found that miR-375 has prognostic and predictive values in LCNEC. Increased miR-375 expression has been associated with poor prognosis in LCNEC, with a median survival of 8-12 months [28][29][30]. These studies assessed the predictive value of mir375 as a biomarker for chemotherapy-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that miR-375 has prognostic and predictive values in LCNEC. Increased miR-375 expression has been associated with poor prognosis in LCNEC, with a median survival of 8-12 months [28][29][30]. These studies assessed the predictive value of mir375 as a biomarker for chemotherapy-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs modulate several intracellular signaling pathways and induce many effects. These molecules can be classified according to their effects on tumor-suppressive miRNAs and oncogenic miRNAs (oncomirs) [ 12 , 15 ].…”
Section: Regulation Of Mirnas In Key Signaling Pathways Involved In N...mentioning
confidence: 99%
“…Although studies are available regarding the role of several miRNAs in lung cancer tissue in the prognosis of patients with NSCLC, these have mainly evaluated cell lines in in vitro models, and few data are currently available on human lung cancer tissue [ 15 ].…”
Section: Role Of Mirnas As Prognostic Factors In Patients With Nsclcmentioning
confidence: 99%